Alterações de glândulas salivares em pacientes com hepatite C crônica - Soraya de Mattos Camargo Grossmann (2010)
Background and aims. The sialotropism of HCV has been implicated in the pathogenesis of oral extrahepatic manifestations, as xerostomia and sialadenitis, in patients with chronic hepatitis C. The aim of this study was to investigate the prevalence of HCV RNA in saliva and salivary glands and its possible association with xerostomia, hyposalivation and sialadenitis in patients with chronic hepatitis C.Methods. 136 patients with confirmed diagnosis of chronic hepatitis C (anti-HCV and HCV RNA PCR positive) were included in this cross sectional study, after exclusion of HIV and/or HBV coinfection, and patients under HCV treatment. The study was approved by Ethical Board of UFMG. HCV RNA was investigated by nested RT-PCR insaliva samples of all patients and in minor salivary gland of 65 patients. Xerostomia was evaluated and non-stimulated (NSSF) and stimulated (SSF) salivary flows were measured. NSSF and SSF .0.1ml/min and .0.7ml/min, respectively, were indicative of hyposalivation. Clinical evidence of sialadenitis and the histopathological presence ofinflammatory infiltration in salivary glands were also evaluated. Oral exam were performed in all patients. The possible associations among the different variables, including demographical data and medical history, were tested by univariate and multivariate analyzes using Stata 10.0 and EPIINFO 3.4.3 software.Results. The sample comprised 71 (52.2%) men and 65 (47.8%) women, and mean age of 58.1 years. Xerostomia was reported by 48/136 (35.3%) patients. Hyposalivation was observed in 16 (11.8%) NSSF samples and in 21 (15.4%) SSF (p=NS). HCV RNA wasdetected in saliva of 53/136 (39.0%) patients and in salivary glands of 12/65 (18.5%) patients. Six (9.2%) of 65 patients had concomitant the HCV RNA in saliva and salivary glands. In 11/136 (8.0%) patients, xerostomia and hyposalivation were observed simultaneously, and HCV RNA was detected in saliva and salivary glands in 2/11 (18.2%) patients. Although none showed clinical evidence of sialadenitis, in 31/65(47.7%) patients histological diagnosis of sialadenitis could be made. HCV RNA was 13 detected in saliva samples of 12/31 (38.7%) and in salivary glands of 3/31 (9.7%) patients with sialadenitis. Oral mucosal conditions were diagnosed in 76/136 (55.9%) patients. There was not association among the studied variables.Conclusion. Xerostomia, hyposalivation and sialadenitis are frequent in patients with CHC. However, these alterations of salivary glands could not be associated with the presence of HCV RNA in saliva or salivary glands, in disagreement with sialotropism of HCV described in the literature. However, our results do not exclude the possibility ofsalivary glands disorders in chronic hepatitis C patients as a consequence of immune mechanism prompted by virus. Thus, further investigations of the pathogenic aspects of this association are necessary.